Statistical properties and material partial factors of ECC material based on shear failure member - Yi, Shixiang; Tang, Zhongping; Shi, Wei; Feng, Fan; Liu, Xiang (Frontiers in Materials, 2025)
Engineered Cementitious Composite (ECC) material, as a hybrid material, also has uncertainties. In addition, the shear failure mechanism of reinforced ECC (R-ECC) member is different from that of ordinary reinforced concrete (RC) member, and a new material partial factor of ECC is needed. This paper conducted experiments for the statistical mechanics of ECC strength. The shear failure test data of 36 R-ECC members were collected, and four representative bearing capacity calculation models were also collected and assessed. Then, the limit state function of the shear capacity of R-ECC beams was derived, and the reliability indexes were calculated. To evaluate the ECC material partial factor reasonably, it was calibrated. The results indicate that ECC strength obeys a normal distribution, and the coefficient of variation can be taken as 6.0%. The calculated reliability index will increase with the increase of the material partial factor and the increase of the ratio k between dead load and live load. Considering the different k values comprehensively, for the guidelines GB 50068-2018, CSA S806, ACI 440.2R, CIDAR, fIB TG 9.3 and UK TR 55, the recommended values for the material partial factor are 1.20, 1.10., 1.15, 1.55, 1.05, and 1.05, respectively.